Faktor yang Berhubungan dengan Mutu Pelayanan Kesehatan Ibu dan Anak di Puskesmas Campalagian - Heriyati Heriyati (Universitas Sulawesi Barat, 2025)
Campalagian Community Health Center is one of the health centers in Campalagian District, Polewali Mandar Regency, the problem in this study is related to the examination of pregnant women according to standards has not met the SPM target, maternal health services according to standards have also not reached the target and there is a maternal and child mortality rate every year in the Campalagian Community Health Center work area. The purpose of this study was to determine the factors related to the quality of maternal and child health services at Campalagian Community Health Center. This study used a quantitative method with a cross-sectional approach. The number of samples in this study was 94 respondents, Data collection was carried out using a questionnaire instrument. The results of the study showed that the variables that were significantly related to the quality of maternal and child health services were, continuity of service p = (0.002), Access to services p = (0.001), and comfort p = (0.005), while the variables that did not have a significant relationship with the quality of maternal and child health services were Interpersonal Relations p = (0.952). The conclusion of this study is that there is a significant relationship between the variables of service continuity, access to services, comfort with the quality of maternal and child health services, and there is no significant relationship between the variables of interpersonal relationships with the quality of maternal and child health services at the Campalagian Community Health Center.